Analisis Kinerja Keuangan Perusahaan Umum Daerah (PERUMDA) Air minum di Provinsi Sumatera Utara - Rifka fadila; Anggun Sari; Regina Regina; nur husna; Erwinsyah Erwinsyah (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study aims to analyze the influence of the Operational Ratio, Cash Ratio, Collection Effectiveness, and Solvency on the Return on Equity (ROE) of Regional Water Supply Companies (PERUMDA Air Minum) in North Sumatra Province. The research employed a quantitative approach using multiple linear regression analysis via SPSS software. Data were obtained from audited financial statements of PERUMDA Air Minum companies. The results show that all independent variables simultaneously have a significant effect on ROE, with an F-value of 7.830 and a significance level of < 0.001. Partially, the Operational Ratio has a significant negative effect, while Collection Effectiveness has a significant positive effect on ROE. The Cash Ratio was found to be insignificant. The coefficient of determination (R²) of 0.380 indicates that 38% of ROE variation is explained by the independent variables. After removing outliers through the boxplot test, the regression model satisfied classical assumption tests and showed normally distributed data. This research contributes empirical evidence emphasizing the importance of operational efficiency and collection performance in improving the financial outcomes of regional enterprises. The findings provide valuable insights for management in developing effective financial strategies while ensuring sustainable public service.